TANGGUNG JAWAB HUKUM ANGGOTA MILITER DALAM KASUS KORUPSI MELALUI PERADILAN KONEKSITAS ANTARA KPK DAN TNI - Mohammad Mahmudi; Ludfi Ludfi (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
Corruption is a serious threat to development, social stability and public trust in government. The involvement of members of the military in corruption cases is a serious concern, given the strategic role played by the military in maintaining national security. This article describes the urgency of judicial connectivity between the Corruption Eradication Commission (KPK) and the Indonesian National Armed Forces (TNI) in handling corruption cases involving members of the military. The research uses normative legal analysis methods by collecting data through literature studies, recognizing the legal responsibilities of military members in cases of corruption under existing regulations. This article also analyzes legal challenges that arise, such as hierarchies and loyalties within military institutions, which can affect the judicial process. The establishment of a judiciary connection between the KPK and the TNI is considered important to maintain the integrity of military institutions, ensure transparency in the handling of corruption cases, and strengthen the eradication of corruption. overall. The advice given is to strengthen cooperation between the KPK and the TNI and to increase the capacity of connectivity court judges to respond to legal challenges that arise in the handling of corruption cases for members of the military.